Leadership Challenges Impacting Employee Performance & Retention in the United States (US) Pharmaceutical Industry (Companies) - Blacksmith, Ivan (Digital Repository of Theses - SSBM Geneva, 2024)
The pharmaceutical sector in the United States encounters a range of complex difficulties that have a substantial impact on worker performance and retention. The issues that give support to dimensions of management and have a significant effect on employee experiences and workforce productivity when performing relative tasks. This research employs qualitative research methodology to explore the complex intricacies of leadership difficulties within the pharmaceutical industry. The area of this research relies on the fundamental principles of qualitative research, which places a strong emphasis on conducting a thorough investigation into the experiences, viewpoints, and behaviors of those who participate in the pharmaceutical sector. The data gathering process was completed through a questionnaire guide and the instruments used were semi-structured interviews, focus group discussions, and analyzing current literature. These instruments are strategically used to gather valuable and contextually significant information from workers, executives, HR experts, and other key stakeholders. vii The targeted demographic consists of persons who are actively engaged in the pharmaceutical sector, including workers at different hierarchical positions, human resources professionals, and organizational leaders. The approach of purposive sampling has been used to allow researchers to deliberately choose participants who possess the necessary information and viewpoints to effectively address the goals of this research. The main objective of this research is to give insights into the challenges faced by leaders and management in the pharmaceutical industry and the effect these challenges have on the performance and retention of staff. The results provide a holistic comprehension of the intricate dynamics in operation. The study instrument functions as a tool to uncover the complex nature of leadership difficulties and their impact on the pharmaceutical industry. This study has the potential to provide significant insights for both academic researchers and industry professionals. This study uses a qualitative approach to analyze leadership problems to enhance comprehension of their effects on employee outcomes, as well as the subsequent influence on talent retention and performance in the pharmaceutical sector of the United States. The major aim of this study is to give insights into techniques and interventions that may effectively improve leadership practices and promote employee well-being in this crucial industry.